Abo blood groups and helicobacter pylori cagA infection: Evidence of an association - Mattos, D. E. [UNESP]; Cintra, J. R.; Brandão de Mattos, C. C.; Nakashima, F. [UNESP]; Silva, R. C.M.A.; Moreira, H. W. [UNESP]; de Mattos, L. C. (FapUNIFESP (SciELO), 2010)
Diseases resulting from Helicobacter pylori infection appear to be dependent on a host of genetic traits and virulence factors possessed by this microorganism. This paper aimed to investigate the association between the ABO histo-blood groups and H. pylori cagA infections. Genomic DNA samples (n = 110) of gastric biopsies obtained from patients with endoscopic diagnosis of peptic ulcers (n = 25) and chronic active gastritis (n = 85) were analyzed by PCR using specific primers for the cagA gene. Of the samples, 66.4% (n = 73) tested positive and 33.6% (n = 37) negative for the gene. The cagA strain was predominant in peptic ulcers (n = 21; 84.0%) compared with chronic active gastritis (n = 52; 61.2%) (p = 0.05; OR 3.332; 95% CI: 1.050-10.576). Additionally, the cagA strain was prevalent in the type O blood (48/63; 76.2%) compared with other ABO phenotypes (25/47; 53.2%) (p = 0.01; OR 2.816; 95% CI: 1.246-6.364). These results suggest that H. pylori cagA infection is associated with the O blood group in Brazilian patients suffering from chronic active gastritis and peptic ulcers.
Keywords: ABO blood groups; CagA strain; Chronic active gastritis; H. pylori infection; Peptic ulcers